Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics: Main Volume 2021
DOI: 10.18653/v1/2021.eacl-main.54
|View full text |Cite
|
Sign up to set email alerts
|

Query Generation for Multimodal Documents

Abstract: This paper studies the problem of generating likely queries for multimodal documents with images. Our application scenario is enabling efficient "first-stage retrieval" of relevant documents, by attaching generated queries to documents before indexing. We can then index this expanded text to efficiently narrow down to candidate matches using inverted index, so that expensive reranking can follow. Our evaluation results show that our proposed multimodal representation meaningfully improves relevance ranking. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Question Generation (QG) has a wide range of applications, such as generating questions for exams (Jia et al, 2021;Lelkes et al, 2021;Dugan et al, 2022) or children's story books (Zhao et al, 2022;Yao et al, 2022), recommending questions for users in a dialogue system (Shukla et al, 2019;Laban et al, 2020), improving visual (Li et al, 2018;Lu et al, 2022) or textual question-answering tasks (Duan et al, 2017;Lewis et al, 2019a;Zhang and Bansal, 2019;Sultan et al, 2020;Lyu et al, 2021), asking clarification questions (Rao and DaumĆ© III, 2019;Ren et al, 2021), and generating queries for SQL or multimodal documents (Kim et al, 2021). * Equal Contribution Previous works on QG are mainly under the openbook setting, which aims to generate questions based on factoid or human-generated short answers under the assumption that there is access to external knowledge like retrieved documents or passages (Du et al, 2017;Zhao et al, 2018;Kim et al, 2019;Fei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Question Generation (QG) has a wide range of applications, such as generating questions for exams (Jia et al, 2021;Lelkes et al, 2021;Dugan et al, 2022) or children's story books (Zhao et al, 2022;Yao et al, 2022), recommending questions for users in a dialogue system (Shukla et al, 2019;Laban et al, 2020), improving visual (Li et al, 2018;Lu et al, 2022) or textual question-answering tasks (Duan et al, 2017;Lewis et al, 2019a;Zhang and Bansal, 2019;Sultan et al, 2020;Lyu et al, 2021), asking clarification questions (Rao and DaumĆ© III, 2019;Ren et al, 2021), and generating queries for SQL or multimodal documents (Kim et al, 2021). * Equal Contribution Previous works on QG are mainly under the openbook setting, which aims to generate questions based on factoid or human-generated short answers under the assumption that there is access to external knowledge like retrieved documents or passages (Du et al, 2017;Zhao et al, 2018;Kim et al, 2019;Fei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…After demonstrated that feeding a large pre-trained model input questions alone without any external knowledge can lead to competitive results with retrieval-based methods on open-domain question-answering benchmarks, there is an increasing interest in the closed-book setting. This closed-book setting is appealing in practice and can be widely applied, e.g., in question suggestion (Laban et al, 2020;, query recommendation (Kim et al, 2021), and other practical settings where extensive external knowledge is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Lexical approaches use the terms that appear in a user's query to identify and score documents that contain the same terms (e.g., using an approach like BM25 over an inverted index). Lexical approaches like BM25 [35] fail to understand semantic relationships in different scenarios [17]. A major drawback of this approach is that it is limited to documents that use the exact terms that the user searches for, which can potentially affect the recall.…”
Section: Introductionmentioning
confidence: 99%